Impact of the pandemic on global food security - Adriana Fillol Mazo (Universidad Hemisferios, 2023)
The Covid-19 pandemic has had a profound impact on global food security, having exacerbated the drivers of hunger, such as economic recession, political instability, or the disruption and fluidity of the global food supply chain. However, the negative impact of Covid-19 on food security reflects the difficult situation of the current global food security governance system. In this work our general objective is to analyze the ways through which the Covid-19 pandemic has affected world food security. Our specific objective is to study and deepen how the impact of Covid-19 on food security reflects structural problems in global food security governance, in order to provide recommendations on how the international community should respond to prevent a public health crisis from triggering a global food crisis.